The difference of oral hygiene status between ethnic group Minang and Sundanese in Pangalengan aged 26-45 years old - Rinaldy, Efru; Muhibat, Sjazili; Suwargiani, Anne Agustina (Padjadjaran Journal of Dentistry, 2013)
Introduction: Indonesia has a lot of different languages, customs, and food. Each ethnic has a distinctive food of each such Minang ethnic happy with spicy foods and coconut milk, while Sundanese pleased with foods that are sweet and dry. The purpose of this study was to determine the status of oral hygiene ethnic group Minang and Sundanese. Methods: This research use descriptive research. The method used in the study are the type of total sampling method. Samples will be selected according to the criteria of the indigenous people the Minang ethnic and Sundanese ethnic who live in the village Pangalengan district as many as 33 people Minang ethnic and 66 people Sundanese ethnic as a control. Results: Results showed a p-value of oral hygiene status in Minang ethnic communities and Sundanese ethnic communities in Pangalengan is 0.261. Oral hygiene status in Minang ethnic communities in the district Pangalengan are in the medium category with the numbers 2.7, while the Sundanese people are in the medium category with the numbers 2.4. Conclusion: The conclusions of this study is there is no difference of oral hygiene status between Minang ethnic and Sundanese ethnic in Pangalengan age of 26-45 years.